MAKANAN HANTARAN PADA UPACARA PERKAWINAN DI DESA SUNGAI ABU KECAMATAN HILIRAN GUMANTI KABUPATEN SOLOK PROVINSI SUMATERA BARAT - Santi, Titen Darlis; Yusuf, Liswarti; Sofnitati, Sofnitati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
The background of this research is the lack knowledge of sungai Abu citizen about the a series of delivery events, which brought indigenous food, the tools used to carry food customs and customary meaning of food brought to the delivery and implementation of events that play a role in treating food only mothers aged 60 years. The purposes of this study are (1) to describe the implementation of a series of ceremonial delivery, (2) describe the type of custom foods delivery, (3) describe the equipment used to carry the customary food delivery (4) expresses the meaning of food delivery at the ceremony. The research is a qualitative research, the research object is the customary food that is brought in delivery event in the village of sungai Abu. The instrument used in this study is the observation, interview and documentation. Data are analyzed using data reduction, data presentation, drawing conclusions and verification. The results showed that the delivery event in Sungai abu village be held in the second day of marriage ceremony, conducting a series of delivery events in the village of sungai abu has two stages: preparation before the event and conducting a series of traditional ceremonies, the type of food served at the delivery ceremony are 23 species and which as a symbol of niniak mamak and interest to both families. Keywords: Food Delivery, Wedding Ceremony.